Financing coastal management initiatives in Klang District, Selangor, Malaysia - Asmawi, M. Zainora; Mahamod, Lukman Hakim; Md. Din, Azrin (2011)
Managing natural resources sustainably is essential in this contemporary era of town planning system. This includes managing and planning the invaluable of coastal areas. In this regards, coastal management programmes have been acknowledged as primary approach in delivering the coastal strategies and objectives towards achieving a sustainable coastal development worldwide. As such, this paper suggests that coastal management approach as one key element of town planning system that can and should make a substantial contribution to planning coastal areas in Malaysia. It has many positive implications to the environmental, social and economic sectors. In addition, financial element has become a significant attribute in implementing coastal management initiatives. Thus, the underlying objectives of this research were to examine and analyse the relationship between the implementation of coastal management initiatives and financial aspect. The study was undertaken in Klang District, based on data collection from interviews, consisting of government officials at various levels and coastal management practitioners. Furthermore, secondary data was obtained from various government agencies, such as the Town and Country Planning Department and Klang Municipal Council. The outcomes can further be used by the planning authority as part of their tools in controlling and regulating development and budgeting annually. This study offers input in planning education by addressing the integration of coastal management, town planning and financial elements which are very relevant with today’s current global changes on environment as a whole.